Safety and Security Issues, Gender-Based Violence and Militarization in the Time of Armed Conflict: The Experiences of Internally Displaced People From Marawi City - Veloso, Diana Therese M. (Frontiers in Human Dynamics, 2022)
This study delves into the experiences of armed conflict and displacement among civilians, who evacuated from the Islamic City of Marawi to nearby cities and municipalities in Northern Mindanao, as well as other parts of the Philippines, to escape the clashes between ISIS-affiliated extremists and security forces in 2017. Drawing upon in-depth interviews and focus group discussions with survivors of armed conflict and duty-bearers, such as government employees, heads of non-government organizations (NGOs), doctors, faculty members and administrators of educational institutions, and volunteers who aided in relief efforts, this research identifies the safety and security issues and vulnerabilities confronting internally displaced people (IDPs) from Marawi City, who are predominantly racial, ethnic, and religious minorities. This study investigates the heightened risk for gender-based violence among women and girls and men and boys in conflict zones and the challenges in the promotion of their safety and well-being. This paper examines the dynamics of gender-based violence and the respondents’ experiences of private, community-based, and state-sponsored violence in conflict zones and the risk of further violence upon their return to Marawi City. This research also examines the experiences of militarism among IDPs and their views of and coping strategies under Martial Law, which was declared in Mindanao on the first day of the Marawi Siege in May 2017. This study illuminates the nuances in the experiences of IDPs living in traditional evacuation centers and alternative home-based evacuation arrangements, the service needs they confront, and the support systems and interventions available to them. The researcher highlights the links between racial, ethnic, gender, and social class inequality in the Philippines and the vulnerability of IDPs, given their dismal living conditions and the absence of normalization in their lives due to the prolonged siege. This paper highlights the intersections between private and public violence, the human rights issues confronting IDPs from Marawi City, and the local and international responses to their situation.